Velocidad de cierre del ductus arterioso tras terapia con ibuprofeno en prematuros, Hospital Regional de Loreto junio - diciembre 2020 - Segovia Barrientos, Boris Valery (2022)
Patent ductus arteriosus (PDA) is a frequent condition in preterm newborns (PTNB), which has been associated with complications, sometimes serious in this group of patients, such as bronchopulmonary dysplasia, pulmonary hypertension, enterocolitis necrotizing, intraventricular hemorrhage among others. Within the therapeutic schemes proposed to date, there is none that assesses the magnitude of DAP to provide its treatment. There are standardized treatment protocols that do not take this data into account, so the same therapeutic scheme is provided for all. With the present work, it is proposed to study the speed of closure of the ductus arteriosus with oral ibuprofen therapy, taking into account the various degrees of DAP prior to the start of therapy. This in order to objectify the probable lower need for oral ibuprofen doses in mild cases and higher doses in more severe cases. Having an optimized treatment would improve the patient's condition and would avoid sub-optimal or higher unnecessary doses. Likewise, based on these results, larger studies could be proposed in the future to define exact optimal doses according to the initial magnitude of DAP.